2016
DOI: 10.1111/jofo.12132
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming challenges to morphological and molecular identification of Empidonax flycatchers: a case study with a Dusky Flycatcher

Abstract: ABSTRACT. Flycatchers in the genus Empidonax are among the most difficult avian taxonomic groups to identify to species. Observers often rely on calls or songs in the field or detailed morphometrics in the hand to identify species. In January and February 2013, we twice captured an Empidonax flycatcher at the Virginia Zoo in Norfolk, Virginia. After being unable to identify the flycatcher to species level using morphometrics and photographs, we extracted DNA from two tail feathers collected during the second e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Certain bird species and taxonomic groups can be more challenging than others to identify (Rigby et al 2019;Gorleri et al 2022). We found that the species that were detected less often by volunteers were species with more traditionally challenging identification characteristics, such as warblers or Empidonax flycatchers (Heller et al 2016). For example, in our dataset, professional biologists detected 5 times more Wilson's Warblers (Cardellina pusilla), 4.4 times more Yellow-breasted Chats (Icteria virens), and 1.4 times more Yellow-rumped Warblers (Setophaga coronata) than citizen scientists.…”
Section: Discussionmentioning
confidence: 85%
“…Certain bird species and taxonomic groups can be more challenging than others to identify (Rigby et al 2019;Gorleri et al 2022). We found that the species that were detected less often by volunteers were species with more traditionally challenging identification characteristics, such as warblers or Empidonax flycatchers (Heller et al 2016). For example, in our dataset, professional biologists detected 5 times more Wilson's Warblers (Cardellina pusilla), 4.4 times more Yellow-breasted Chats (Icteria virens), and 1.4 times more Yellow-rumped Warblers (Setophaga coronata) than citizen scientists.…”
Section: Discussionmentioning
confidence: 85%
“…We avoided the temptation to attempt to take the taxonomic treatment to a newer authority list (e.g., Gill & Donsker, 2014 ; Navarro-Sigüenza & Peterson, 2004 ; Peterson & Navarro-Sigüenza, 2006 ) because taxonomic splitting, which has dominated recent years of taxonomic work, would cause considerable confusion of names applied to older records. Hence, we reduced the initial, highly redundant set of names to 1,027 names that coincided with the taxonomy of the American Ornithologists’ Union ( AOU, 1998 ), except that we merged Empidonax traillii and E. alnorum , in light of very frequent confusion in identification ( Heller et al, 2016 ). This step was achieved based on long years of experience with Mexican bird taxonomy, plus occasional consultation of the literature ( Monroe & Sibley, 1993 ; Peters, 1931–1987 ) and online ( http://avibase.bsc-eoc.org/ ) resources.…”
Section: Methodsmentioning
confidence: 99%
“…We avoided the temptation to attempt to take the taxonomic treatment to a newer authority list (e.g., Gill & Donsker 2014;Navarro-Sigüenza & Peterson 2004;Peterson & Navarro-Sigüenza 2006) because taxonomic splitting, which has dominated recent years of taxonomic work, would cause considerable confusion of names applied to older records. Hence, we reduced the initial, highly redundant set of names to 1027 names that coincided with the taxonomy of the American Ornithologists' Union (AOU 1998), except that we merged Empidonax traillii and E. alnorum, in light of very frequent confusion in identification (Heller et al 2016). This step was achieved based on long years of experience with Mexican bird taxonomy, plus occasional consultation of the literature (Monroe & Sibley 1993;Peters 1931Peters -1987 and online (http://avibase.bsc-eoc.org/) resources.…”
Section: Methodsmentioning
confidence: 99%